Incidence of suicidality in people with depression over a 10-year period treated by a large UK mental health service provider. Issue 6 (24th November 2021) - Francis, Emma R.; Fonseca de Freitas, Daniela; Colling, Craig; Pritchard, Megan; Kadra-Scalzo, Giouliana; Viani, Natalia; Chaturvedi, Jaya; Denee, Tom R.; Kerr, Cicely; Desai, Mitesh; Scott, Gemma; Shetty, Hitesh; et al.
Summary: We describe the incidence of suicidality (2007–2017) in people with depression treated by secondary mental healthcare services at South London and Maudsley NHS Trust ( n = 26 412). We estimated yearly incidence of 'suicidal ideation' and 'high risk of suicide' from structured and free-text fields of the Clinical Record Interactive Search system. The incidence of suicidal ideation increased from 0.6 (2007) to 1 cases (2017) per 1000 population. The incidence of high risk of suicide, based on risk forms, varied between 0.06 and 0.50 cases per 1000 adult population (2008–2017). Electronic health records provide the opportunity to examine suicidality on a large scale, but the impact of service-related changes in the use of structured risk assessment should be considered.